2017
DOI: 10.1016/j.polymer.2017.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Local and segmental motions of the mobile amorphous fraction in semi-crystalline polylactide crystallized under quiescent and flow-induced conditions

Abstract: Local and segmental motions of the mobile amorphous fraction Local and segmental motions of the mobile amorphous fraction in semi-crystalline polylactide crystallized under quiescent and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…The decrease of the physical aging rate with increasing crystallinity degree has been reported for several semiecrystalline polymers, including polypropylene [59], poly (phenylene sulfide) [60], or PEEK [61]. Monnier et al [62] observed that the structural recovery functions between semiecrystalline PLA crystallized under quiescent or floweinduced conditions were similar, with an aging rate of 1.1 ± 0.1 J/decade, if rescaled to the MAF content. These results are consistent with ours.…”
Section: Influence Of the Constraint Nature On The Physical Aging Kinmentioning
confidence: 75%
“…The decrease of the physical aging rate with increasing crystallinity degree has been reported for several semiecrystalline polymers, including polypropylene [59], poly (phenylene sulfide) [60], or PEEK [61]. Monnier et al [62] observed that the structural recovery functions between semiecrystalline PLA crystallized under quiescent or floweinduced conditions were similar, with an aging rate of 1.1 ± 0.1 J/decade, if rescaled to the MAF content. These results are consistent with ours.…”
Section: Influence Of the Constraint Nature On The Physical Aging Kinmentioning
confidence: 75%
“…We can envisage that the kinetic endotherm observed in our work is an enthalpy recovery peak that mostly arises out of the molecular orientation due to the shear exerted on the polymer jet below T g during the spinning process. Such recovery occurs only in the mobile amorphous fraction (MAF) and could not be attributed to the rigid amorphous fraction (RAF) or mesophase. , We will bring further evidence on the origin of the recovery peak and its relation to the structural features of ES fibers in Section .…”
Section: Resultsmentioning
confidence: 94%
“…The samples were quenched using liquid nitrogen prior to cutting to prevent ductile failure from the blade. A similar sampling approach was developed to observe the relaxation of FIC precursors in poly­(lactic acid) using fast calorimetric techniques, but crystallization behaviors were not observed . Prior to placing the sample on the FSC chip, a thin layer of thermally stable silicone fluid (Wacker AK 60000) was applied to the surface of the chip to aid in heat transfer and to prohibit the sample from fusing to the chip.…”
Section: Methodsmentioning
confidence: 99%